Acute secondary pancreatitis to giant hiatal hernia. A case report - Roberto Lázaro Blanco Sosa; José Ángel Cuesta Del Sol (Medisur)
In grade IV hiatal hernias, the stomach herniates together with other abdominal organs. The association of acute pancreatitis is rare. A case of a 61-years-old patient who came to the Emergency Room for intense abdominal pain associated with abundant vomiting for two days is presented. She reported a history of chronic gastritis, dyspeptic disorders for five months, and recent weight loss. Additional blood tests were ordered, which showed alteration of pancreatic enzymes consistent with inflammation of the organ. Imaging studies reported the presence of a giant hiatal hernia, with part of the stomach and duodenum inside. Delayed surgical treatment was performed (hiatal herniorrhaphy with Toupet fundoplication). Analysis of pancreatic enzymes, together with imaging methods such as computed axial tomography, esophagogastroduodenoscopy and barium study of the esophagus-stomach and duodenum contributed to the formulation of the diagnosis.